Ageing leads to selective type II myofibre deterioration and denervation independent of reinnervative capacity in human skeletal muscle - Oscar Horwath; Marcus Moberg; Sebastian Edman; Andrew Philp; William Apró (Experimental Physiology)
Abstract Age‐related loss of muscle mass and function is underpinned by changes at the myocellular level. However, our understanding of the aged muscle phenotype might be confounded by factors secondary to ageing per se, such as inactivity and adiposity. Here, using healthy, lean, recreationally active, older men, we investigated the impact of ageing on myocellular properties in skeletal muscle. Muscle biopsies were obtained from young men (22 ± 3 years, n = 10) and older men (69 ± 3 years, n = 11) matched for health status, activity level and body mass index. Immunofluorescence was used to assess myofibre composition, morphology (size and shape), capillarization, the content of satellite cells and myonuclei, the spatial relationship between satellite cells and capillaries, denervation and myofibre grouping. Compared with young muscle, aged muscle contained 53% more type I myofibres, in addition to smaller (−32%) and misshapen (3%) type II myofibres (P < 0.05). Aged muscle manifested fewer capillaries (−29%) and satellite cells (−38%) surrounding type II myofibres (P < 0.05); however, the spatial relationship between these two remained intact. The proportion of denervated myofibres was ∼2.6‐fold higher in old than young muscle (P < 0.05). Aged muscle had more grouped type I myofibres (∼18‐fold), primarily driven by increased size of existing groups rather than increased group frequency (P < 0.05). Aged muscle displayed selective deterioration of type II myofibres alongside increased denervation and myofibre grouping. These data are key to understanding the cellular basis of age‐related muscle decline and reveal a pressing need to fine‐tune strategies to preserve type II myofibres and innervation status in ageing populations.